The Effectiveness of Rational Emotive Behavior Therapy Group Counseling to Reduce Loneliness through Increasing Self-Adjustment for New College Students - Maranata, Phina; Wibowo, Mungin Eddy; Sugiharto, Dwi Yuwono Puji (Jurnal Bimbingan Konseling, 2019)
This study aims to examine the effectiveness of rational emotive behavior therapy group counselingto reduce the loneliness through increasing self-adjustment to new college students at Borneo Tarakan University. The research method used was an experimental design, the design of pre-test – post-test control group involving 16 subjects who purposively selected from 79 students. The result showed that there was an indirect effect given to the rational emotive behavior therapy group counselingtowards loneliness through increasing self-adjustment to new college students. This study provides an understanding for counselors regarding rational emotive behavior therapy group counselingin reducing the loneliness through increasing self-adjustment to new college students.